Efektivitas Penerapan Strategi Penghimpunan Dana Zakat Dan Wakaf - Muhammad Abdul Aziz; Achmad Hasyim Masruri; Abdi Ari Sandi; Muhammad Dzikky Firman Syah (xxxx-xxxx, 2021)
Baitul Qur'an Social Fund Institution is one of the social fund institutions in Ponorogo which is located in Gontor, Mlarak, Ponorogo. This institution was established in 2015 and under the management of the Baitul Qur'an Islamic Boarding School Sholeh Children's. the unique features of this institution is that in raising funds uses the ZISCO system strategy, ZISWAF pickup which was adopted from the YDSF Al-Fatah Surabaya system. This system is carried out by visiting several donors in order to pick up the donations that will be distributed. This has improved the good relationship between muzakki and institutions, thus strengthening the friendship and sense of kinship between the two parties. The funds that have been collected will be distributed to ashnaf who really need the funds through several programs at the Baitul Qur'an Social Fund Institution.